Research and application of supporting technologies for improving success rate of water injection well testing - XU Guochen, LIU Xiaowen (Youqicang pingjia yu kaifa)
To address the challenges of test instrument obstruction and the suboptimal deployment of concentric stratified water injection in the Subei complex fracture block oilfields, an innovative approach involving the use of a hollow rod for pipe cleaning was introduced. This method focused on two key areas: the implementation of a flowback preventing water dispenser and the application of chemical sand control technology to maintain the cleanliness of the water injection pipe. In addition, a polymer gel profile control system was designed to mitigate the disparities between layers, aiming to minimize the influence of stratum grade differences on measurement and adjustment processes. This suite of supporting technologies has been applied to testing wells a total of thirteen times. The on-site tests have demonstrated that this approach is effective in preventing the obstruction of testing instruments and in simplifying the deployment process for layered water injection. Notably, the success rate of testing wells for these annual supporting measures reached 100 %, marking a significant achievement. Furthermore, the overall success rate of concentric layered water injection wells increased from 74.4 % to 84.4 %. The implementation of this method offers a dual advantage of reducing costs and enhancing efficiency, particularly in the context of optimizing fine water injection.